Efforts to Improve Creative Writing Skills for Short Stories Through the Application of the Concept Learning Model with Canva Media - Martini; Dessy Wardiah; Yessi Fitriani (Journal of Practice Learning and Educational Development, 2025)
This study aims to: (1) To determine the increase in the ability to write creative short stories of class V students of SDN 4 Banyuasin III through the application of the concept learning model with Canva media; (2) To determine the percentage of increase in the ability to write creative stories of class V students of SDN 4 Banyuasin III through the application of the concept learning model with Canva media . This type of research is action research which is carried out in 2 cycles and each cycle consists of two meetings. This research was conducted in class V of SDN 4 Banyuasin III, Banyuasin Regency. Data collection technique conducted through test activities. The results of this study indicate that: (1) Through the application of the Concept Learning learning model with Canva Media, the ability of class V students of SDN 4 Banyuasin III to write creative short stories can be improved; (2) The percentage increase in the ability of class V students of SDN 4 Banyuasin III to write creative short stories from cycle I to cycle II is 12.55%.